EFEKTIVITAS PENGALIHAN PEGAWAI KPK MENJADI PEGAWAI ASN BERDASARKAN PERATURAN PEMERINTAH NO. 41 TAHUN 2020 - Savira Putri Rhaudah (2022)
This study aims to test the Effectiveness of Transferring KPK Employees to ASN Employees based on Government Regulation no. 41 of 2020. This thesis is a type of normative juridicial research. This study uses a problem approach, namely the Statue Approach and the Conceptual Approach. The type of data used in this study uses secondary data by collecting data using the Research Library. The analysis technique in the thesis uses the Content Analysis method. The results of this study indicate that changing the status of a KPK employee to an ASN employee can change the work systematics that apply to the KPK because it must comply with ASN regulations. And the impact that can be seen on the KPK body is the weakening that occurs by the KPK body because of a code of ethics that must be applied by KPK employees and supervised by KemenPAR-RB and BKN